EVALUASI PELAYANAN KUALITAS AGENCY BANK â€œXâ€ DI SURABAYA - Nurmianto, Eko; Trisunarno, Lantip; Sudjono, Hary (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
Research objective is to determine difference between customerâ€™s expectation towards service quality and management perception on customer expectation. Research advantages (1) to obtain clear information on customersâ€™ expectation and perception as well as to improve its service quality, and (2) to know the problem inside the agency. Methodology Customer Questionnaires consist of 4 parts, Part I: 8 qualitatif question (customer demography), Part II : 17 Customer Perception Questions, Part III : 17 Customer Expectation Questions, Part IV: Open Question for Weighted Importance of 5 SERVQUAL dimension. Management Questionnaires consist of 3 parts, Part I : 4 questions (management demography and working duration), Part II : 17 customer perception questions, management on customer expectation towards service execution, Part III : Open Question for Weighted Importance of 5 SERVQUAL dimension. Data Analysis Methodology: Descriptive, Cluster, Discriminant, and Dependency Analysis, SERVQUAL Analisis on Gap 5 and Gap 1. Results : Gap 1 cluster 1 require improvement on variable 5 (service always free from errors), for cluster 2 on variable 10 (if error occur then agency would fix). Gap 5 cluster 1 needs improvement variable 5 (service always free from errors), variable 8 (service always suit to the promises), variable 9 (customer complaint would be honestly responsed), and variable 11 (hospitality of agency Bank staff), for cluster 2 on variable 17 (sympathy agency staff). Based on Importance-Performance Graph, variable which is need to be fixed on cluster 1 is variable 8 (service always suit to the promises). Cluster 2 variable which is need is variable 8 (service always suit to the promises) and variable 10 ((if error occur then agency would fix).